The Compensatory Consumer Behavior Model: How self‐discrepancies drive consumer behavior. Issue 1 (24th May 2016) - Mandel, Naomi; Rucker, Derek D.; Levav, Jonathan; Galinsky, Adam D.
Abstract: Consumer goods and services have psychological value that can equal or exceed their functional value. A burgeoning literature demonstrates that one source of value emerges from the capacity for products to serve as a psychological salve that reduces various forms of distress across numerous domains. This review systematically organizes and integrates the literature on the use of consumer behavior as a means to regulate self‐discrepancies, or the incongruities between how one currently perceives oneself and how one desires to view oneself (Higgins, 1987). We introduce a Compensatory Consumer Behavior Model to explain the psychological consequences of self‐discrepancies on consumer behavior. This model delineates five distinct strategies by which consumers cope with self‐discrepancies: direct resolution, symbolic self‐completion, dissociation, escapism, and fluid compensation . Finally, the authors raise critical questions to guide future research endeavors. Overall, the present review provides both a primer on compensatory consumer behavior and sets an agenda for future research.